Features of seeds formation of genus Zinnia L. species and sorts cultivated at the Crimean foothill zone - Tukach Svetlana Igorevna (Hortus Botanicus, 2017)
Seed productivity study of some Zinnia L. genus representatives was condusted. The highest ratio of seed productivity showed Zinnia violacea Cav. species in the case of direct sowing cultivation method (9.2 g seeds per plant) and Zinnia haageana Regel – in the case of a propagation method (4.4 g seeds from plants). It was found, that seed productivity of Zinnia L. genus stays the same regardless of the bloom doubleness, as semifloscule flowers produce well developed seeds, the same as tubular flowers. The conducted correlation analysis showed that the impact of semifloscule and tubular flowers on inflorescence productivity is different: "the number of well developed seeds in inflorescence" is in direct proportion to "the number of well developed seeds of tubular flowers" and determines "the total amount of seeds in inflorescence" (i=0,79). According to the seed productivity criteria of Zinnia L. species, the Crimean foothill zone was determined as a promising region for flower and seed cultivation, when a direct sowing method is used.